TINJAUAN ETIKA IKLAN POP-UP DALAM SIARAN LANGSUNG SEPAK BOLA BRI LIGA 1 PADA PLATFORM STREAMING VIDEO.COM - Taqwim, Akhsani; Yuga Komara, Adiyama; Sukmawan, M. Nur Syifa (Universitas Muhammadiyah Jakarta, 2024)
Disturbances in advertising can occur from anywhere, including advertising that appears during a football match. This violates the norms written in the Indonesian Advertising Ethics. This research aims to determine the standards that apply to Indonesian Advertising Ethics. This research uses descriptive qualitative to describe and interpret the consequences or effects that occur in the appearance of this advertisement. The analysis results show that the large number of advertisements appearing in one round of a football match reduces the audience's attention when watching the match.